2021
DOI: 10.1021/acs.est.1c05796
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Poisonous Plastic Particles: Microplastics as a Vector for Cyanobacterial Toxins Microcystin-LR and Microcystin-LF

Abstract: The potential of microplastics to act as a vector for micropollutants of natural or anthropogenic origin is of rising concern. Cyanobacterial toxins, including microcystins, are harmful to humans and wildlife. In this study, we demonstrate for the first time the potential of microplastics to act as vectors for two different microcystin analogues. A concentration of up to 28 times from water to plastic was observed for the combination of polystyrene and microcystin-LF achieving toxin concentrations on the plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 45 publications
2
38
1
Order By: Relevance
“…In addition, of the studied MPs, PS exhibited the greatest adsorption capability toward both MC-LR and IOM, with the adsorption capability reaching 843 and 1470 µg/g, respectively. Recently, it was demonstrated that the hydrophilic MC-LR [29] had lower adsorption onto PE and PS compared to the more hydrophobic Microcystins variant MC-LF [16]. However, the current study revealed that the adsorption capability of MC-LR to hydrophilic PMMA accounted for 61.8% of that on PS.…”
Section: Adsorption Isothermscontrasting
confidence: 65%
See 1 more Smart Citation
“…In addition, of the studied MPs, PS exhibited the greatest adsorption capability toward both MC-LR and IOM, with the adsorption capability reaching 843 and 1470 µg/g, respectively. Recently, it was demonstrated that the hydrophilic MC-LR [29] had lower adsorption onto PE and PS compared to the more hydrophobic Microcystins variant MC-LF [16]. However, the current study revealed that the adsorption capability of MC-LR to hydrophilic PMMA accounted for 61.8% of that on PS.…”
Section: Adsorption Isothermscontrasting
confidence: 65%
“…Generally, MCs are predominant in toxin-producing algal cells, but can be released into the water when the algal cells are lysed under stress; hence, the MC concentration in the water could reach several micrograms per liter. Previously, it was documented that MCs can be adsorbed by PS microplastics [16]. This was also confirmed in a recent study [17].…”
Section: Introductionsupporting
confidence: 70%
“…In addition, the spatial and temporal variability of MP and NP in the water, air or food is unknown which does not allow for standardized sampling protocols (63). The second step includes the hazard characterization which is hampered by the fact that plastic particles can present three types of hazards, physical, chemical and biological, which makes the identification and characterization of hazards very extensive and complex (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Moreover, MP and NP are a multidimensional contaminant, differing in size, shape, polymer type, and additive cocktail, which could determine their toxicity (64,65).…”
Section: Discussionmentioning
confidence: 99%
“…Toxic microcystins (MCs), produced by blue-green cyanobacterial, pose a worldwide threat to humans and wildlife [1,2]. When orally ingested, MCs can be transported to the liver by organic anion transport proteins [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…MCs are a class of monocyclic heptapeptides that share a common structure of cyclo-(D-Ala 1 -L-X 2 -D-isoAsp 3 -L-Z 4 -Adda 5 -D-isoGlu 6 -Mdha 7 ) [9]. Due to the variable amino acids at positions 2 and 4, multiple variants have been identified [1,10]. Among MC variants, the most widespread and toxic congener MCLR was widely studied [11].…”
Section: Introductionmentioning
confidence: 99%